Pomiędzy "gender" a "queer". Kwestia uświadomienia tożsamości seksualnej na przykładzie filmu "Sala samobójców" Jana Komasy = Between the "gender" and "queer". Using the film "Suicide Room" by Jan Komasa as an example to explain problems with sexual identity awareness - Rawski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to analyze the process of finding, shaping and becoming aware of the sexual identity by Dominik Santorski ? the main character in the film "Suicide Room". The problem seems to be interesting due to the fact of such a brave pioneering publication in the Polish cinema of the issue of undefined sexuality.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie